Exploring Sustainability Implications of Transitions to Agroecology: a Transdisciplinary Perspective. (24th December 2022) - Schwarz, Gerald; Vanni, Francesco; Miller, David; Helin, Janne; Pražan, Jaroslav; Albanito, Fabrizio; Fratila, Mihaela; Galioto, Francesco; Gava, Oriana; Irvine, Katherine; Landert, Jan; Quero, Alba Linares; et al.
Summary: Successful transitions to agroecology require shared understanding of the sustainability implications of transitions for food systems. To gain such understanding, a transdisciplinary approach is increasingly called for by funders, end users of research and scientists. Transdisciplinary processes were used in the UNISECO project to develop strategic pathways that enable transitions to agroecology in case studies across Europe. These strategic pathways were combined with scenarios of EU food systems in 2050, in which combinations of agroecological farming and food consumption practices were assessed. These were then reviewed considering selected UN Sustainable Development Goals (SDGs) as a reference for discussing the sustainability implications of transitions to agroecology. Sustainability implications were identified for several SDGs including Zero Hunger (SDG 2), Quality Education (SDG 4), Responsible Consumption and Production (SDG 12), Climate Action (SDG 13) and Life on Land (SDG 15). Key factors contributing to the sustainability of transitions to agroecology are: i) mature social capital and improved farmer knowledge of the benefits of agroecological practices; ii) strengthened collaborative actions and collective institutions to increase negotiating power within the value‐chain; and, iii) changes in consumer behaviour and diets. These factors highlight the need for a food system perspective in transitions to agroecology and supporting policies. This in turn highlights the meaningful role of transdisciplinary research in strengthening the sustainability of European food systems. Abstract : Les transitions réussies vers l'agroécologie nécessitent une compréhension partagée des implications des transitions en termes de durabilité pour les systèmes alimentaires. Pour parvenir à une telle compréhension, une approche transdisciplinaire est de plus en plus demandée par les bailleurs de fonds, les utilisateurs finaux de la recherche et les scientifiques. Des processus transdisciplinaires ont été utilisés dans le projet UNISECO pour développer des voies stratégiques qui permettent des transitions vers l'agroécologie dans des études de cas à travers l'Europe. Ces voies stratégiques ont été combinées avec des scénarios sur des systèmes alimentaires de l'Union européenne en 2050, dans lesquels des combinaisons d'agriculture agroécologique et de pratiques de consommation alimentaire ont été évaluées. Les résultats ont ensuite été examinés en tenant compte de certains objectifs de développement durable (ODD) des Nations Unies comme référence pour examiner les implications en termes de durabilité des transitions vers l'agroécologie. De telles implications ont été identifiées pour plusieurs ODD, notamment Faim zéro (ODD 2), Éducation de qualité (ODD 4), Consommation et production responsables (ODD 12), Action pour le climat (ODD 13) et Vie terrestre (ODD 15). Les principaux facteurs contribuant à la durabilité des transitions vers l'agroécologie sont: i) un capital social mature et une meilleure connaissance par les agriculteurs des avantages des pratiques agroécologiques; ii) des actions collaboratives et des institutions collectives renforcées pour accroître le pouvoir de négociation au sein de la chaîne de valeur; et, iii) des changements dans le comportement des consommateurs et les régimes alimentaires. Ces facteurs soulignent la nécessité d'une perspective de système alimentaire dans les transitions vers l'agroécologie et les politiques d'accompagnement. Cela met ainsi en évidence le rôle significatif de la recherche transdisciplinaire dans le renforcement de la durabilité des systèmes alimentaires européens. Abstract : Ein erfolgreicher Übergang zur Agrarökologie erfordert ein gemeinsames Verständnis über die Auswirkungen auf die Nachhaltigkeit von Lebensmittelsystemen. Um ein solches Verständnis zu erlangen, wird von Geldgebenden, der Forschung und ihren Endnutzern und ‐nutzerinnenzunehmend ein transdisziplinärer Ansatz gefordert. Im Rahmen des UNISECO‐Projekts wurden transdisziplinäre Prozesse eingesetzt, um strategische Pfade zu entwickeln. Sie sollen den Übergang zur Agrarökologie in Fallstudien in ganz Europa ermöglichen. Diese strategischen Pfade wurden mit Szenarien der EU‐Lebensmittelsysteme im Jahr 2050 zusammengeführt und in Kombination mit agrarökologischen Landwirtschafts‐ und Ernährungsgewohnheiten bewertet. Als Referenz für die Diskussion der Auswirkungen auf die Nachhaltigkeit dienten ausgewählte UN‐Ziele für nachhaltige Entwicklung (Sustainable Development Goals, SDGs). Die Auswirkungen wurden für mehrere SDGs identifiziert, darunter Kein Hunger (SDG 2), chancengerechte und hochwertige Bildung (SDG 4), nachhaltiger Konsum und Produktion (SDG 12), Klimaschutz und Anpassung (SDG 13) und Leben an Land (SDG 15). Schlüsselfaktoren, die zur Nachhaltigkeit des Übergangs zur Agrarökologie beitragen, sind: i) gewachsenes Sozialkapital und verbessertes Wissen in der Landwirtschaft über die Vorteile agrarökologischer Verfahren; ii) verstärkte gemeinschaftliche Aktionen und kollektive Institutionen, um die Verhandlungsmacht innerhalb der Wertschöpfungskette zu erhöhen; und iii) Veränderungen im Konsumverhalten und in der Ernährung. Diese Faktoren unterstreichen die Notwendigkeit, Übergänge zur Agrarökologie und unterstützende Maßnahmen aus der Perspektive der Lebensmittelsysteme zu betrachten. Hieraus wird wiederum die bedeutende Rolle einer transdisziplinären Forschung zur Stärkung der Nachhaltigkeit europäischer Lebensmittelsysteme deutlich.